Heart transplantation at a single tertiary adult congenital heart disease centre: Too little, too late?. (1st January 2021) - Merás, Pablo; Riesgo-Gil, Fernando; Rybicka, Justyna; Barradas-Pires, Ana; Smith, John; Kempny, Aleksander; Brookes, Paul; Simon, Andre; Gatzoulis, Michael A.
Abstract: Background: Heart failure (HF) is the leading cause of death in adults with congenital heart disease (ACHD). Heart transplantation can be an effective therapy for them, albeit unfavourable anatomy, end-organ damage, pulmonary vascular disease, HLA sensitization and lack of robust selection criteria currently limit its application. Methods: Consecutive CHD patients considered for heart or combined heart and lung transplantation at our tertiary ACHD centre between 2000 and 2018 constitute our study population. Baseline characteristics and outcome, including transplantation and death, were obtained for all patients from designated databases, medical records and the UK Office for National Statistics. Results: From a total of more than 9000 active ACHD patients under follow-up, 166 (median age 40.4 years) fulfilled inclusion criteria, with a broad spectrum of underlying diagnosis: univentricular heart 22.3%, systemic right ventricle 22.3%, systemic-to-pulmonary shunts and Eisenmenger syndrome 16.3%, left sided valvular lesions 14.5%, tetralogy of Fallot 12.7%, CHD associated with cardiomyopathy 4.8% and other 7.2%. There was a high overall mortality with 39.2% of patients dying over a median follow-up of 2.7 years. A minority of patients (22.9%) were eventually listed and only 13.3% from the 166 patients were actually transplanted. Survival at 1 year after transplantation was 81.8% and remained high long-term (65.5% at 15 years). We describe herewith in detail characteristics and outcome of our cohort and present the transplantation pathway followed. Conclusion: Of the small number of patients with ACHD considered for heart transplantation at a large tertiary centre, there was high overall mortality, with only a fraction of patients being actually transplanted. Patients who received transplantation, however, had a good outcome. Better patient selection and timing are clearly warranted so that more ACHD patients are considered and potentially benefit from this effective form of therapy. Highlights: Heart failure is the leading cause of death in adults with congenital heart disease (CHD). Heart transplantation can be an effective therapy, but there is uncertainty about patient selection criteria and timing for transplantation. There is high overall mortality among CHD patients with heart failure, with good long-term outcomes after transplantation. Only a small percentage of patients assessed finally undergo transplantation.